Validitas Perangkat Pembelajaran Konsep Fluida Berbasis Science Technology Engineering Art Mathematic (STEAM) Berorientasi Education For Sustainable Development (ESD) - Rezki Widarti; Nur Khoiri; Fenny Roshayanti (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
The purpose of this research is to obtain learning sets that can be integrated with ESD-oriented STEAM on valid fluid material. The type of research is research and development using the Borg and Gall model which is simplified into three steps consisting of introduction, development, and testing. Data collection techniques by providing questionnaire validation experts and educational practitioners, and documentation. The data analysis technique consists of two techniques, the first technique is quantitative in the form of presentation validation results of learning devices, and the second technique is qualitative which comes from the validator's suggestions and comments. The results showed that the ESD-oriented STEAM-based learning sets had very valid results. Expert validation results for syllabus 93%, lesson plans 81%, e-module 88% and worksheet 78%. The results of the validation of educational practitioners for the syllabus have a percentage of 92%, lesson plans 94% for E-modules 91% and worksheets 91%